Multidrug-Resistant Organisms Infection on Mortality of Burn Patients at Public Hospital X in Jakarta: A Retrospective Study - Veronica, Raja Merlinda; Kumalawati, July; Rumende, Cleopas Martin; Nainggolan, Leonard; Simadibrata, Marcellus; Shatri, Hamzah; Yunir, Em; Wardhana, Aditya; Nelwan, Erni Juwita; Rustam, Musfardi (Kesmas, 2024)
Susceptibility to infection and increasing antibiotic resistance put burn patients at risk of developing infections caused by multidrug-resistant organisms (MDRO). This condition can progress to sepsis, increasing morbidity and mortality. This retrospective cohort study employed the medical record data of patients treated at Public Hospital X in Jakarta, Indonesia, from January 2020 to June 2022. Of 160 subjects, most were aged <60 years (82.5%) and had comorbidities (16.88%). The most common cause of burns was fire (86.25%). The use of medical devices was 90.63%, with a 14-day median length of stay. The most common gram-negative MDRO pathogens were K. pneumoniae (29.91%), Enterobacter sp (22.32%), and Acinetobacter (20.54%); 45% of patients infected with MDRO died. The bivariate analysis found an increased risk of death due to MDRO infection in burn patients (RR 1.103; 95%CI 1.004-1.211, p-value = 0.046). After adjusting for role variables (age, comorbidities, total body surface area, use of medical devices, length of stay) and from multivariate analysis, the confounding variables for MDRO infection and mortality were length of stay and age. MDRO infection increases the mortality rate in burn patients. Mortality in burn patients due to MDRO infection is greater than non-MDRO.